Field emission from oriented tin oxide rods - Deshpande, A. C.; Koinkar, Pankaj M.; Ashtaputre, S. S.; More, Mahendra A.; Gosavi, S. W.; Godbole, P. D.; Joag, Dilip S.; Kulkarni, S. K. (Thin Solid Films, 2006)
Tin oxide (SnO2) films were grown on silicon substrates by a wet chemical route. It was found from scanning electron microscopy investigations that oriented SnO2 rods normal to the substrates were obtained. Field emission studies were carried out in diode configuration in an all metal ultra high vacuum chamber at a base pressure similar to 1.33 x 10(-8) mbar. The `onset' field required to draw 0.1 mu A/cm(2) current density from the emitter cathode was found to be similar to 3.4 V/mu m for SnO2 rods. The field emission current and applied field follows the Folwer-Nordheim relationship in low field regime. The observed results indicate that the field emission characteristics of chemically grown SnO2 structures are comparable to the vapor grown nanostructures. (c) 2006 Elsevier B.V. All rights reserved.
Keywords: field emission; microstructures; scanning electron microscopy; tin oxide